Confronting a Church in Controversy - Hinze, Bradford E. (Paulist Press, 2022)
"The aim of this book is to provide a reliable framework and theological orientation for considering the central factors that have contributed to the clergy sex abuse controversy in order to face the detrimental repercussions for the future of the church and to explore realistic responses based on an assessment of the various issues involved"--